Dealing with aggressive patients in the practice. (2nd January 2021) - Devlin, Clare
Abstract : Managing aggressive patients is something that challenges a practice at the best of times. Dr Clare Devlin, Medicolegal Consultant at Medical Protection, offers advice on handling difficult situations